Measurement of the forward-backward charge asymmetry and extraction of sin2θWeff in pp̄→Z/γ*+X→e+e-+X events produced at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2008)
We present a measurement of the forward-backward charge asymmetry (AFB) in pp̄→Z/γ*+X→e+e-+X events at a center-of-mass energy of 1.96 TeV using 1.1fb-1 of data collected with the D0 detector at the Fermilab Tevatron collider. AFB is measured as a function of the invariant mass of the electron-positron pair, and found to be consistent with the standard model prediction. We use the AFB measurement to extract the effective weak mixing angle sin2θWeff=0.2326±0.0018(stat)±0.0006(syst). © 2008 The American Physical Society.